2022
DOI: 10.31083/j.rcm2305152
|View full text |Cite
|
Sign up to set email alerts
|

TakoTsubo Syndrome: First an Acute Coronary Vasculitis and Then Prolonged Myocarditis?

Abstract: Since its initial description by Japanese investigators 30 years ago, TakoTsubo Syndrome (TTS) has variously been regarded as a form of acute coronary syndrome and also as a form of cardiomyopathy (or more accurately, a myocarditis). There is actually good evidence that TTS embodies both of these concepts, and the main purpose of this review is to present data that they occur sequentially. The initial phase of the disorder (over perhaps the first 48 hours post onset of symptoms) represents a form of vasculitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…The issue of coronary vasculitis as a basis for subsequent myocardial dysfunction in TTS has been appreciated in two previous studies, independent of our previous postulate of sequential pathogenesis (21). In 2020, Montone et al demonstrated in a cohort of 101 TTS patients, that acute coronary flow retardation (TIMI-2 flow) was associated with an increased risk of in-hospital acute heart failure (37).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The issue of coronary vasculitis as a basis for subsequent myocardial dysfunction in TTS has been appreciated in two previous studies, independent of our previous postulate of sequential pathogenesis (21). In 2020, Montone et al demonstrated in a cohort of 101 TTS patients, that acute coronary flow retardation (TIMI-2 flow) was associated with an increased risk of in-hospital acute heart failure (37).…”
Section: Discussionmentioning
confidence: 87%
“…Very recently, we have proposed that TTS begins as an acute coronary vasculitis, and evolves into a myocarditis of variable severity and duration (21). However, little has been done to determine whether the putative second phase results from the first.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation